2022
DOI: 10.1038/s41598-022-06054-5
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of apical lymph node metastasis in patients with high-risk stage III colon cancer

Abstract: The effect of apical lymph node (APN) metastasis on the prognosis of colon cancer is unknown. The present study investigated the impact of APN metastasis on the prognosis of the patients with high-risk stage III colon cancer. This retrospective multi-institutional study included patients with pathological high-risk stage III colon cancer who underwent surgery between April 2009 and December 2014. Clinicopathological factors were examined by univariate and multivariate analyses to clarify independent risk facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 24 publications
(44 reference statements)
0
12
0
Order By: Relevance
“…30 It is possible that having a clear definition of the central lymph nodes (D3 volume) allows for the complete removal of these nodes in most patients, thus reducing the incidence of recurrence in them. 17,18,24 When analyzing the articles on both parallel progression theory 37,38 (both the primary tumor and lymph node metastases are polyclonal and seeding occurs in multiple waves) or linear progression theory 39,40 (cancer cells of primary tumors reach the apical lymph node along the adjacent lymph node pathway, leading to distant metastases), a common denominator can be found: radical resection may have a therapeutic effect by removing occult metastatic lymph nodes, implying that tumor biology plays a crucial role in the evolution of the disease. Lal et al 41 have recently shown a relationship between the primary tumor immune response and lymph node yield, resulting in improved survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 It is possible that having a clear definition of the central lymph nodes (D3 volume) allows for the complete removal of these nodes in most patients, thus reducing the incidence of recurrence in them. 17,18,24 When analyzing the articles on both parallel progression theory 37,38 (both the primary tumor and lymph node metastases are polyclonal and seeding occurs in multiple waves) or linear progression theory 39,40 (cancer cells of primary tumors reach the apical lymph node along the adjacent lymph node pathway, leading to distant metastases), a common denominator can be found: radical resection may have a therapeutic effect by removing occult metastatic lymph nodes, implying that tumor biology plays a crucial role in the evolution of the disease. Lal et al 41 have recently shown a relationship between the primary tumor immune response and lymph node yield, resulting in improved survival.…”
Section: Discussionmentioning
confidence: 99%
“…This may imply that a more extensive mesenterectomy could lead to improved survival rates. 17 The aim of the current study was to re-stratify patients with stage I-III right-sided colon cancer based on the presence or absence of OTC and/or metastatic lymph nodes in the different levels of surgical dissection and to investigate the impact on oncologic outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Colon cancer (CC) is a common malignancy of the gastrointestinal tract and the third leading cause of cancer-related mortality worldwide ( 1 ). A large number of studies have shown that lymph node metastasis (LNM) is an independent risk factor for the prognosis of patients with CC ( 2 , 3 ). In addition, the scope of surgery for patients with CC should take full account of the preoperative lymph node status to avoid overtreatment ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Activated cancer cells developing high invasive potential contribute to tumor spread through metastasis process via blood vessels and lymphatic system ( Pretzsch et al, 2019 ). Metastatic CRC (mCRC) patients, clinically described for the presentation of distant lymph node metastasis, have a high mortality rate ( Ishii et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%